Complementary physical methods for the detection of carious lesions - Monteiro, Douglas Roberto [UNESP]; Sampaio, Caio [UNESP]; Fabregat, Beatriz Diaz [UNESP]; Carmona, Wilmer Ramirez [UNESP]; Oliveira, Evelyn Carmo [UNESP]; dos Santos Gomes Alves, Guilherme; Pessan, Juliano Pelim [UNESP] (IOP Publishing, 2023)
Dental caries is a biofilm-dependent disease, resulting from the slow, but progressive mineral loss from tooth structures caused by exposure to fermentable carbohydrates. Occlusal and approximal surfaces are often the most affected tooth sites for caries development, due to their intrinsic stagnation sites, which facilitates biofilm accumulation and hinders the action of salivary buffers. The intricate anatomy of occlusal surfaces, with pits and fissures, makes the detection of early lesions by visual and tactile inspection a difficult process, often involving unnecessary dental destruction due to false positive detection. Likewise, the detection of approximal lesions may sometimes be unfeasible by conventional clinical examination. Considering that accurate early detection is paramount for the prevention of further tooth destruction, increasing interest have been targeted to diagnostic tools that can be used alone or in association with conventional visual-tactile approaches. This chapter presents and discusses diagnostic tools based on physics principles, including conventional and digital intraoral radiography, laser fluorescence, quantitative light-induced fluorescence, fiber-optic transillumination, and cone beam computed tomography. The physical principles of each method, their main advantages and disadvantages, as well as the available scientific evidence, are addressed for each method.